Comparison of the Effect of Giving Amlodipine in the Morning and Nighttime Effect on Patient Blood Pressure Decrease Profile Hypertension with Comorbid Type 2 Diabetes Mellitus - abidah, novariaa khabib; Ria Utami, Primanitha; Susanti, Irma (Journal of Herbal, Clinical and Pharmaceutical Science (HERCLIPS), 2026)
Someone who has blood pressure >140/90 mmHg is also called hypertension. Therapy for hypertensive patients is carried out for life. Amlodipine is a CCB class which is the first line therapy for elderly hypertensive patients which is consumed once a day and can be given in the morning or evening. This study aims to determine whether there is a difference in the blood pressure decrease values of patients who take amlodipine in the morning and evening with comorbid type 2 diabetes mellitus. This research uses a descriptive observational method with a cross-sectional approach. The sample in this study consisted of 80 patients who were divided into two groups, each group consisting of 40 patients. In the first group, patients took amlodipine in the morning and in the second group, patients took amlodipine in the evening. The results of the statistical test using Wilcoxon have a value for the difference between the reduction in systolic blood pressure in the morning and evening, p=0.184 and for the difference in the reduction in diastolic blood pressure in the morning and evening, p=0.420, so there is no significant comparison between the reduction in systolic and diastolic blood pressure in the morning and evening.